Aurimastris, new genus of the treehopper tribe Amastrini (Hemiptera, Membracidae, Smiliinae) - Evangelista, Olívia; Sakakibara, Albino M. (Zootaxa, 2007)
A new genus and two new species are described from Brazil: Aurimastris new genus; Aurimastris expansa new species (type species) (Mato Grosso), and Aurimastris otina new species (Rio de Janeiro). A key to Amastrini genera and illustrations are given, including the male genitalia.